Electrocatalytic Activity of Asymmetrical Cobalt Phthalocyanines in the Presence of N Doped Graphene Quantum Dots: The Push‐pull Effects of Substituents. Issue 5 (7th February 2019) - Nkhahle, Reitumetse; Sekhosana, Kutloano Edward; Centane, Sixolile; Nyokong, Tebello
Abstract: A series of Co phthalocyanine (CoPc) derivatives and their respective nitrogen doped graphene quantum dot conjugates were used as catalysts towards the electrooxidation of hydrazine. Using a glassy carbon electrode as a support for the electrocatalysts, through cyclic voltammetry and chronoamperometry, the effects of combining the CoPcs with the nitrogen doped graphene quantum dots (NGQDs) were studied. The general observations made were that the NGQDs improve the catalytic activity of the CoPcs in both the π‐π stacked and covalently linked conjugates by increasing the sensitivities and lowering the limits of detection with values as low as 0.43 μM being recorded. Abstract :